Religious and Gender Issues In the Tradition of Basurung and the Polygamy of Banjar Tuan Guru in South Kalimantan - Nadhiroh, Wardatun (Pascasarjana IAIN Pontianak, 2017)
Banjar is among the largest ethnic groups in Kalimantan Island, concentrated in South Kalimantan and a small part of other Kalimantan. As an adherent of Islam, Banjar ethnic group is very religious. Tuan guru, a designation for respected ulama, play as a role model in everyday life. The have a gathering for studies (pengajian) that are always attended by a large number of followers (jama'ah). People want to be close to this elites, making them as apart of their family. For the sake of this effort, the female jama’ah often 'basurung' of offering to be married by the tuan guru. As a parent they also offer their daughter to marry him. Banjar women will feel honored when they marry a tuan guru, although it turns out to become “an informal wife.” Her family will also be very proud to be able to be bond to a respected tuan guru. As a result, it is no wonder that there are many tuan guru in South Kalimantan who have more than one wife. This paper discusses the culture of basurung initiated by the women of Banjar ethnic group using standpoint of feminism analysis. The work attempts to see the women's points of view, especially in relation to the tuan guru's polygamy culture that occurs within Banjar ethnic group.